Magog’s Church of Sainte-Marguerite-Marie and the Architectural Dynamics Between Two of Québec’s Founding Institutions During the Twentieth Century: The Roman Catholic Church and the Corporate Industrial Manufactory / L’église Sainte-Marguerite-Marie de Magog et la dynamique architecturale entre deux institutions fondatrices du Québec au xxe siècle : l’Église catholique et la manufacture industrielle - Beaudoin, Caroline (Revue de Bibliothèque et Archives nationales du Québec)

(untitled) (Bibliothèque et Archives nationales du Québec, 2012)
This case study conducts a spatial and visual analysis of Magog’s church of Sainte-Marguerite-Marie, located in the Eastern Townships of Québec, based on the plans designed by Sherbrooke architect Joseph Aimé Poulin between 1946 and 1949. The working class community’s social history will be considered in terms of the factory workers’ collective commitment to build a rare and exceptional church in the shadow of the Dominion Textile Company’s imposing factory. The intent is to illustrate how the relative monumentality of the church and its streamlined design respond to the factory both directly and indirectly. The building is not only a product of the architect’s creative vision and technical logic and skill; his clients’, the factory workers’, expectations and motivations merit significant consideration as well. The professional climate of religious architecture during the period also deserves attention, as does the environment within which the building was inserted, and how that building responded to its existing surrounding urban landscape. Finally, this essay presents the church’s architecture as a rather extra-ordinary example of the modern design influence inserted into an otherwise marginalized neighbourhood historically rooted in traditional values, practices and beliefs, positioned at the crossroads between the textile industry and the Roman Catholic Church.